Pengaruh Inflasi, Bank Size, CAR, dan FDR terhadap Tingkat NPF Bank Victoria Syariah Tahun 2013-2021 dengan Pendekatan Robust Regression - Lelis Nabila Falabibah; Rendra Erdkhadifa (Universitas Muhammadiyah Surabaya, 2023)
Non Performing Financing shows the level of problem financing in Islamic banks ranging from substandard to non-performing groups caused by bank external and internal factors. The purpose of this study was to determine the effect of external and internal bank factors on the NPF level of Bank Victoria Syariah. The research approach uses a quantitative approach and associative type of research to determine the relationship between inflation, bank size, CAR, and FDR variables on Bank Victoria Syariah's NPF. The sample in this study is Bank Victoria Syariah's quarterly financial reports for 2013 to 2021 including data on NPF, bank size, CAR, and FDR along with published data on Bank Indonesia's inflation from 2013-2021. The process of data analysis using a robust regression analysis-S estimation. The results of this research show that inflation, bank size, and CAR have an influence on NPF. The FDR variable shows no effect on the NPF level of Bank Victoria Syariah.